2020
DOI: 10.5155/eurjchem.11.4.304-313.2033
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of diversely substituted pyrazolo[1,5-a]pyrimidine derivatives promoted by ultrasound irradiation in water and their antibacterial activities

Abstract: A green synthetic route leading to the discovery of a series of diversely substituted pyrazolo[1,5-a]pyrimidines, having CO2Et group embedded at position-2 has been unraveled in this article. A series of formylated active proton compounds that were chosen to react with a carboxylate substituted-3-aminopyrazole under ultrasonic irradiation in the presence of a mild acid as a catalyst and aqueous ethanol medium afforded the desired products. The molecular structures of all these synthesized compounds were establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Indeed, these heterocycles possess many active sites that make them favorable precursors for the synthesis of novel heterocyclic molecular systems capable of exhibiting a wide spectrum of activity. Moreover, they are used as antibacterial, [3,4] Tropomyosin receptor kinases (Trks), [5] anticancer, [6,7] anti-inflammatory, [8] and antitumor agents. [9] Recently, Das et al synthesized a series of substituted pyrazolo [1,5-a]pyrimidine derivatives via a green synthetic route, which show potential antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, these heterocycles possess many active sites that make them favorable precursors for the synthesis of novel heterocyclic molecular systems capable of exhibiting a wide spectrum of activity. Moreover, they are used as antibacterial, [3,4] Tropomyosin receptor kinases (Trks), [5] anticancer, [6,7] anti-inflammatory, [8] and antitumor agents. [9] Recently, Das et al synthesized a series of substituted pyrazolo [1,5-a]pyrimidine derivatives via a green synthetic route, which show potential antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Recently, Das et al synthesized a series of substituted pyrazolo [1,5-a]pyrimidine derivatives via a green synthetic route, which show potential antibacterial activity. [3] Zhang et al reported the synthesis and inhibitory potency against Trk of a novel pyrazolo [1,5-a]pyrimidine. [5] The α-(benzoylamino)-β-substituted acrylic amides derivatives of pyrazolo [1,5-a]pyrimidine were tested in vitro for their antiproliferative activity, and they exhibited potent anticancer activity in HeLa and HepG 2 cell lines.…”
Section: Introductionmentioning
confidence: 99%